Insights into the Electronic Structure of a U(IV) Amido and U(V) Imido Complex. Issue 21 (14th March 2022) - Köhler, Luisa; Patzschke, Michael; Bauters, Stephen; Vitova, Tonya; Butorin, Sergei M.; Kvashnina, Kristina O.; Schmidt, Moritz; Stumpf, Thorsten; März, Juliane
Abstract: Reaction of the N ‐heterocylic carbene ligand i PrIm (L 1 ) and lithium bis(trimethylsilyl)amide (TMSA) as a base with UCl4 resulted in U(IV) and U(V) complexes. Uranium's +V oxidation state in (HL 1 )2 [U(V)(TMSI)Cl5 ] (TMSI=trimethylsilylimido) (2 ) was confirmed by HERFD‐XANES measurements. Solid state characterization by SC‐XRD and geometry optimisation of [U(IV)(L 1 )2 (TMSA)Cl3 ] (1 ) indicated a silylamido ligand mediated inverse trans influence (ITI). The ITI was examined regarding different metal oxidation states and was compared to transition metal analogues by theoretical calculations. Abstract : In the compound [U(V)(TMSI)Cl5 ], uranium could be stabilized in the rare +V oxidation state proven by HERFD XANES measurements. In the complex, an inverse trans influence (ITI) was uncovered. Quantum chemical calculations show this effect to be dependent on the electronic situation on the metal centre, thus increasing with higher oxidation state.